PENERAPAN DIGITALISASI KOLEKSI ETNOGRAFIKA UNTUK MENINGKATKAN JUMLAH PENGUNJUNG PADA MUSEUM NAGARI DR. SAWIRMAN DI NAGARI TOBOH GADANG KABUPATEN PADANG PARIAMAN - Sawirman Sawirman (BULETIN ILMIAH NAGARI MEMBANGUN, 2022)
The function of modern museums is not only to store the collection but also for education, training, and research. To realize this function, I have created several products for the ethnographical collection of the only museum located in Nagari Toboh Gadang, Sintuk Toboh Gadang District, Padang Pariaman Regency, West Sumatra. The museum is Museum Nagari Dr. Sawirman or simply abbreviated as the Museum Nagari in this article. The research and development method was applied. I have made 32 posters and the Museum Nagari website as the learning and researching media in 2021. These posters have been displayed manually inside the museum and on the website https://sawirman.com/museum/. Those posters show the registration numbers, the local language, artifact names in Bahasa Indonesia, collection numbers, type, subtype, length, width, diameter, origin, the material of the artifact, description, the registration date, and the name of the provider or the artifact seller or collection contributor. All those posters have been copyrighted since December 2021. Since some website content has copyright from the Director-General of Intellectual Properties, Patent and Trademark of Ministry of Law and Human Rights, Republic of Indonesia, viewers cannot download and cite the information unless the source is mentioned in a proper citation. Other outputs are a book profile of the Museum Nagari and a keynote speaker certificate.